Investigación y publicaciones de estudiantes de grado y posgrado - Moncada Godoy, German (Portal de la Ciencia, 2015)
DOI: http://dx.doi.org/10.5377/pc.v4i0.1857 Revista Portal de la Ciencia, No. 4, julio 2013: 3-13